Polyethylene resin for rotational molding as well as preparation method and application thereof
By regulating the microstructure of polyethylene resin in rotomolded military packaging boxes, the problems of insufficient impact resistance, environmental stress crack resistance and slow crack expansion resistance are solved, and higher performance requirements are achieved. It is suitable for military packaging boxes. Application.
Patent Information
- Application Number
- CN202411747218.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-12-02
AI Technical Summary
The existing rotomold military packaging boxes have shortcomings in impact resistance, environmental stress crack resistance and slow crack propagation resistance, resulting in damage in critical periods and damage to important materials.
By designing a special structure of rotomolding polyethylene resin to regulate its microstructure, the specific method includes using a mixture of methyl aluminoxane and support silica and adding bis(1-butyl-3-methylcyclopentene to the use of a mixture of methyl aluminoxane and support silica Dienyl)zirconium dichloride and dimethylsilylbis(2-methyl-4-phenylindenidyl)zirconium dichloride in toluene solution, and gas-phase polymerization reaction is carried out to prepare a polyethylene resin with excellent properties. .
The excellent impact resistance, environmental stress crack resistance and slow crack propagation of polyethylene resin are achieved, making rotomold military packaging boxes more reliable and durable in practical applications.
Smart Images

Figure CN119431641A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polyethylene resins, and in particular relates to a polyethylene resin for rotational molding and a preparation method and application thereof. Background Art
[0002] Military packaging boxes are mainly used for the packaging, storage and transportation of military supplies. Traditional military packaging boxes are mainly wooden boxes and iron boxes. As the requirements for packaging products in the transportation and storage of military products become higher and higher, traditional wooden boxes and iron boxes have the problems of easy rot and rust, poor impact resistance, bulky appearance, and inconvenient loading and unloading, which can no longer meet the requirements of existing military supplies for packaging carriers. Under this circumstance, a new generation of roto-molded military packaging boxes has been developed and gradually equipped for use by the troops.
[0003] Roto-molding is a commonly used plastic product processing method, especially suitable for molding large hollow containers. Roto-molded products have the advantages of low internal stress and no seams. The main raw material of roto-molded products is polyethylene resin. Although the current resin can meet the requirements of molding and appearance, it still has serious deficiencies in some key properties such as impact resistance, resistance to environmental stress cracking, and resistance to slow crack propagation. It is reported that during the critical period of earthquake relief, there were cases where roto-molded military packaging boxes dropped by air were seriously damaged due to poor impact strength or insufficient crack resistance, resulting in damage to important disaster relief supplies.
[0004] Patent CN106699943B discloses a polymerization production process for high-rigidity polyethylene rotomolding resin, wherein a mixture of dry powder catalyst and slurry catalyst is added to a nitrogen-protected container, hydrogen, ethylene and butene are introduced into the container, the molar percentage of hydrogen in the container is controlled to be 8-12%, the molar percentage of butene is 4-7%, and the molar percentage of ethylene is 30-40%, and the polymerization is carried out at 80-100°C in the container for 3-9 hours, the polymerization pressure is 0.05-0.1MPa, and the resin is obtained by termination, flash evaporation, centrifugal separation, drying and screening; the dry powder catalyst and slurry catalyst are both ZN catalysts. The polyethylene resin obtained by this method has high tensile properties and high rigidity, but the resistance to environmental stress cracking and slow crack growth of the polyethylene resin has not been studied.
[0005] Patent CN107108993A discloses a rotomolded article, which includes at least one metallocene-catalyzed polyethylene resin, the polyethylene resin includes at least two metallocene-catalyzed polyethylene fractions A and B, wherein the polyethylene resin includes: 25-55% by weight of polyethylene fraction A based on the total weight of the polyethylene resin, wherein fraction A has a melt index MI2 of at least 25.0 g / 10 minutes as measured according to ISO1133, condition D, at 190°C and under a load of 2.16 kg, and a density at least 0.005 g / cm2 higher than that of the polyethylene resin.3 wherein the polyethylene resin has a density of 0.938-0.950g / cm as measured at 23°C according to ASTMD-1505 3 density; as measured according to ISO1133, condition D, at 190°C and under a load of 2.16 kg, the melt index MI2 is 1.0-25.0 g / 10 minutes. The rotomolded polyethylene resin products prepared by the patent have improved mechanical properties and improved processability, but the environmental stress cracking resistance and slow crack growth resistance of the polyethylene resin still need to be further improved. Summary of the invention
[0006] In view of the deficiencies in the prior art, the object of the present invention is to provide a polyethylene resin for rotational molding and a preparation method and application thereof, wherein the polyethylene resin has excellent impact resistance, resistance to environmental stress cracking and resistance to slow crack growth, and is suitable for use in military packaging boxes.
[0007] In order to achieve the above object, according to one aspect of the present invention, there is provided a polyethylene resin for rotational molding, wherein the polyethylene resin is a copolymer of ethylene and α-olefin; the polyethylene resin is subjected to a continuous self-nucleation annealing heat grading test, and the content of the fraction greater than 120°C is 45-55wt%, the content of the fraction of 116-120°C is 15-20wt%, the content of the fraction of 111-115°C is 10-15wt%, the content of the fraction of 100-110°C is 11-15wt%, and the content of the fraction less than 98.5°C is 8-10wt%.
[0008] In some embodiments, the α-olefin is selected from at least one of butene, hexene, and octene.
[0009] In some embodiments, the content of α-olefin in the polyethylene resin is 1.18-1.92 mol %.
[0010] In some embodiments, the polyethylene resin has one or more of the following characteristics:
[0011] The density of the polyethylene resin is 0.931-0.935 g / cm 3 ;
[0012] The weight average sequence length distribution index of the polyethylene resin is 1.15-1.18;
[0013] The polyethylene resin has a melt mass flow rate MFR of 4-9 g / 10 min under the test conditions of 190° C. and a load of 2.16 kg.
[0014] According to another aspect of the present invention, there is also provided a method for preparing the above-mentioned polyethylene resin for rotational molding, comprising the following steps:
[0015] (1) methylaluminoxane and carrier silica are mixed in a mass ratio of 1-2:1, a toluene solution of bis(1-butyl-3-methylcyclopentadienyl)zirconium dichloride and dimethylsilylbis(2-methyl-4-phenylindenyl)zirconium dichloride is added, the mixture is stirred evenly, washed, filtered, and dried to obtain a metallocene catalyst;
[0016] (2) Adding the metallocene catalyst into a Unipol gas phase process polyethylene device, introducing α-olefin and ethylene in a molar ratio of 0.01-0.05:1, introducing hydrogen as a chain transfer agent, and performing a gas phase polymerization reaction at a polymerization temperature of 80-90° C. and a polymerization pressure of 2.0-2.5 MPa to obtain the polyethylene resin for rotational molding.
[0017] In some embodiments, in step (1), the molar ratio of bis(1-butyl-3-methylcyclopentadienyl)zirconium dichloride to dimethylsilylbis(2-methyl-4-phenylindenyl)zirconium dichloride is 1:0.1-0.5.
[0018] In some embodiments, in step (1), the molar ratio of the methylaluminoxane to the sum of bis(1-butyl-3-methylcyclopentadienyl)zirconium dichloride and dimethylsilylbis(2-methyl-4-phenylindenyl)zirconium dichloride is 20-500:1.
[0019] In some embodiments, in step (2), the concentration of hydrogen is 500-1000 ppm.
[0020] In some embodiments, in step (2), the partial pressure of ethylene in the gas phase polymerization reaction is 70-80%.
[0021] According to another aspect of the present invention, there is also provided a use of the above-mentioned polyethylene resin for rotational molding or the polyethylene resin for rotational molding prepared according to the above-mentioned preparation method in a military packaging box.
[0022] Compared with the prior art, the present invention has the following beneficial effects:
[0023] (1) The present invention creatively designs a polyethylene resin for rotational molding with a special structure. By regulating the microstructure of the polyethylene resin, the fraction content within different temperature ranges obtained by continuous self-nucleation annealing thermal grading test of the resin is regulated, so that the polyethylene resin has excellent impact resistance, environmental stress cracking resistance and slow crack growth resistance, and is suitable for use in military packaging boxes.
[0024] (2) The present invention also provides a method for preparing a polyethylene resin, in particular, by adjusting the molar ratio of bis(1-butyl-3-methylcyclopentadienyl)zirconium dichloride and dimethylsilylbis(2-methyl-4-phenylindenyl)zirconium dichloride, a specific metallocene catalyst is designed, so that the polyethylene resin obtained by using the catalyst has excellent impact resistance, environmental stress cracking resistance and slow crack growth resistance. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] In order to make the content of the present invention more clearly understood, the present invention is further described in detail below according to specific embodiments of the present invention in conjunction with the accompanying drawings, wherein:
[0026] Figure 1 This is the melting curve of the polyethylene resin after continuous self-nucleation annealing and thermal classification in Example 1 of the present invention.
[0027] Figure 2 It is the melting curve of the polyethylene resin after continuous self-nucleation annealing and thermal classification in Comparative Example 1 of the present invention. DETAILED DESCRIPTION
[0028] In order to enable those skilled in the art to understand the characteristics and effects of the present invention, the following is a general description and definition of the terms and expressions mentioned in the specification and claims. Unless otherwise specified, all technical and scientific terms used in the text are the common meanings understood by those skilled in the art for the present invention. In the event of a conflict, the definition in this specification shall prevail.
[0029] The theories or mechanisms described and disclosed herein, whether correct or incorrect, should not limit the scope of the present invention in any way, that is, the present invention can be implemented without being limited by any specific theory or mechanism.
[0030] Herein, when describing embodiments or examples, it should be understood that they are not used to limit the present invention to these embodiments or examples. On the contrary, all substitutes, improvements and equivalents of the methods and materials described in the present invention can be included in the scope limited by the claims.
[0031] In this document, in order to make the description concise, not all possible combinations of various technical features in various embodiments or examples are described. Therefore, as long as there is no contradiction in the combination of these technical features, the various technical features in various embodiments or examples can be combined arbitrarily, and all possible combinations should be considered to be within the scope of this specification.
[0032] The present invention provides a polyethylene resin for rotational molding, wherein the polyethylene resin is a copolymer of ethylene and α-olefin; the content of the fraction greater than 120° C. obtained by performing a continuous self-nucleation annealing heat classification test on the polyethylene resin is 45-55wt%. It can be understood that the content can be any specific value among 45wt%, 46wt%, 47wt%, 48wt%, 49wt%, 50wt%, 51wt%, 52wt%, 53wt%, 54wt%, 55wt% or 45 -55wt%; the lamella thickness of the fraction greater than 120°C obtained by performing a continuous self-nucleation annealing thermal grading test on the polyethylene resin is 12-13nm, and it can be understood that the thickness can be any specific value among 12nm, 12.1nm, 12.2nm, 12.3nm, 12.4nm, 12.5nm, 12.6nm, 12.7nm, 12.8nm, 12.9nm, 13nm or any value within the range of 12-13nm.
[0033] The content of the 116-120°C fraction obtained by performing a continuous self-nucleation annealing thermal grading test on the polyethylene resin is 15-20wt%. It is understandable that the content can be any specific value of 15wt%, 16wt%, 17wt%, 18wt%, 19wt%, 20wt% or any value within the range of 15-20wt%. The lamella thickness of the 116-120°C fraction obtained by performing a continuous self-nucleation annealing thermal grading test on the polyethylene resin is 9.5-10nm. It is understandable that the thickness can be any specific value of 9.5nm, 9.6nm, 9.7nm, 9.8nm, 9.9nm, 10nm or any value within the range of 9.5-10nm.
[0034] The content of the 111-115°C fraction obtained by performing a continuous self-nucleation annealing thermal grading test on the polyethylene resin is 10-15wt%. It is understandable that the content can be any specific value of 10wt%, 11wt%, 12wt%, 13wt%, 14wt%, 15wt% or any value within the range of 10-15wt%. The lamella thickness of the 111-115°C fraction obtained by performing a continuous self-nucleation annealing thermal grading test on the polyethylene resin is 7.5-8.0nm. It is understandable that the thickness can be any specific value of 7.5nm, 7.6nm, 7.7nm, 7.8nm, 7.9nm, 8.0nm or any value within the range of 7.5-8.0nm.
[0035] The content of the 100-110° C. fraction obtained by performing a continuous self-nucleation annealing thermal grading test on the polyethylene resin is 11-15wt%. It is understandable that the content can be any specific value of 11wt%, 12wt%, 13wt%, 14wt%, and 15wt%, or any value within the range of 11-15wt%. The lamella thickness of the 100-110° C. fraction obtained by performing a continuous self-nucleation annealing thermal grading test on the polyethylene resin is 6.0-7.0nm. It is understandable that the thickness can be any specific value of 6.0nm, 6.1nm, 6.2nm, 6.3nm, 6.4nm, 6.5nm, 6.6nm, 6.7nm, 6.8nm, 6.9nm, and 7.0nm, or any value within the range of 6.0-7.0nm.
[0036] The content of the fraction less than 98.5°C obtained by performing a continuous self-nucleation annealing thermal grading test on the polyethylene resin is 8-10wt%. It can be understood that the content can be any specific value of 8wt%, 9wt%, 10wt% or any value within the range of 8-10wt%. The lamella thickness of the fraction less than 98.5°C obtained by performing a continuous self-nucleation annealing thermal grading test on the polyethylene resin is 4.5-5.0nm. It can be understood that the thickness can be any specific value of 4.5nm, 4.6nm, 4.7nm, 4.8nm, 4.9nm, 5.0nm or any value within the range of 4.5-5.0nm.
[0037] In the present invention, the continuous self-nucleation annealing thermal classification (SSA) test is a method for classification based on the different crystallization temperatures of different branched segments in polyethylene. The continuous self-nucleation annealing thermal classification generally includes the following steps: (1) heating the sample to above the melting temperature (at least 25°C above the melting temperature) and keeping the temperature constant for a certain period of time to eliminate the thermal history; (2) cooling the sample at a certain cooling rate to a pre-set minimum temperature (this minimum temperature ensures that the sample can crystallize at this temperature), and keeping the temperature constant for a period of time at the minimum temperature; (3) heating the sample at a certain heating rate to the first set self-nucleation temperature T S (generally 25°C higher than the melting temperature) and keep the temperature constant for a period of time; (4) repeat step (2); (5) heat the sample at a certain heating rate to the next set self-nucleation temperature T S (relative to the previous nucleation temperature T S , the next nucleation temperature T S (6) heating the sample at a certain heating rate to the melting temperature set in step (1), and recording the heating melting curve.
[0038] In the continuous self-nucleation annealing thermal grading test of polyethylene, the fraction with a higher melting temperature corresponds to the lamellae with less branch content, thick lamellae and long methylene sequence. The higher the content of the fraction with a higher melting temperature, the greater the rigidity of the material, which is manifested in the mechanical properties of large yield tensile stress and large bending modulus. The present invention designs a specific metallocene catalyst by regulating the molar ratio of bis(1-butyl-3-methylcyclopentadienyl)zirconium dichloride and dimethylsilylbis(2-methyl-4-phenylindenyl)zirconium dichloride, and then regulates the microstructure of the synthesized polyethylene resin, so that the fraction content in different temperature ranges obtained by the continuous self-nucleation annealing thermal grading test is regulated, so that the polyethylene resin has excellent impact resistance, environmental stress cracking resistance and slow crack growth resistance.
[0039] In some embodiments, the α-olefin is selected from at least one of butene, hexene and octene, preferably 1-hexene. In some embodiments, the content of α-olefin in the polyethylene resin is 1.18-1.92 mol%, and it is understood that the content can be any specific value of 1.18 mol%, 1.2 mol%, 1.3 mol%, 1.4 mol%, 1.5 mol%, 1.6 mol%, 1.7 mol%, 1.8 mol%, 1.9 mol%, 1.92 mol%, or any value within the range of 1.18-1.92 mol%.
[0040] In some embodiments, the density of the polyethylene resin is 0.931-0.935 g / cm 3 It is understood that its density can be 0.931 g / cm 3 , 0.932g / cm 3 , 0.933g / cm 3 , 0.934g / cm 3 , 0.935g / cm 3 Any specific value or 0.931-0.935g / cm 3 Any value in the range.
[0041] In some embodiments, the weight average sequence length distribution index of the polyethylene resin is 1.15-1.18, and it can be understood that it can be any specific value of 1.15, 1.16, 1.17, 1.18 or any value within the range of 1.15-1.18. The weight average sequence length distribution index can characterize the uniformity of the lamella thickness distribution. The larger the index, the more uneven the comonomer distribution and the worse the regularity of the material.
[0042] In some embodiments, the Z-average sequence length distribution index of the polyethylene resin is 1.25-1.28. It is understood that it can be any specific value of 1.25, 1.26, 1.27, 1.28 or any value within the range of 1.25-1.28.
[0043] In some embodiments, the melt mass flow rate MFR of the polyethylene resin under the test conditions of 190°C and a load of 2.16 kg is 4-9 g / 10 min. It can be understood that it can be any specific value of 4 g / 10 min, 5 g / 10 min, 6 g / 10 min, 7 g / 10 min, 8 g / 10 min, 9 g / 10 min or any value within the range of 4-9 g / 10 min. In some preferred embodiments, the melt mass flow rate MFR of the polyethylene resin under the test conditions of 190°C and a load of 2.16 kg is 4.5-5.6 g / 10 min.
[0044] According to another aspect of the present invention, there is also provided a method for preparing the above-mentioned polyethylene resin for rotational molding, comprising the following steps:
[0045] (1) methylaluminoxane and carrier silica are mixed in a mass ratio of 1-2:1, a toluene solution of bis(1-butyl-3-methylcyclopentadienyl)zirconium dichloride and dimethylsilylbis(2-methyl-4-phenylindenyl)zirconium dichloride is added, the mixture is stirred evenly, washed, filtered, and dried to obtain a metallocene catalyst;
[0046] (2) Adding the metallocene catalyst into a Unipol gas phase process polyethylene device, introducing α-olefin and ethylene in a molar ratio of 0.01-0.05:1, introducing hydrogen as a chain transfer agent, and performing a gas phase polymerization reaction at a polymerization temperature of 80-90° C. and a polymerization pressure of 2.0-2.5 MPa to obtain the polyethylene resin for rotational molding.
[0047] In some embodiments, in step (1), methylaluminoxane and carrier silica are mixed at a mass ratio of 1-2:1. It is understood that the mass ratio can be any specific value of 1:1, 1.1:1, 1.2:1, 1.3:1, 1.4:1, 1.5:1, 1.6:1, 1.7:1, 1.8:1, 1.9:1, 2:1 or any value within the range of 1-2:1. The present invention can use conventional carrier silica in the art, including but not limited to spherical mesoporous silica carriers and rod-shaped mesoporous silica carriers, and the average particle size of silica is between 20 and 100 microns. In some embodiments, in step (1), the molar ratio of bis(1-butyl-3-methylcyclopentadienyl) zirconium dichloride to dimethylsilylbis(2-methyl-4-phenylindenyl) zirconium dichloride is 1:0.1-0.5. It is understood that the molar ratio can be any specific value of 1:0.1, 1:0.2, 1:0.3, 1:0.4, 1:0.5 or any value within the range of 1:0.1-0.5. In some embodiments, in step (1), the molar ratio of methylaluminoxane to the sum of bis(1-butyl-3-methylcyclopentadienyl) zirconium dichloride and dimethylsilylbis(2-methyl-4-phenylindenyl) zirconium dichloride is 20-500:1, preferably 20-100:1. In some embodiments, the washing can be performed using hexane.
[0048] In some embodiments, in step (2), the molar concentration ratio of the metallocene catalyst to ethylene is 0.2-0.4. In some embodiments, in step (2), the concentration of hydrogen is 500-1000 ppm, preferably 600-800 ppm.
[0049] In some embodiments, in step (2), the partial pressure of ethylene in the gas phase polymerization reaction is 70-80%. It is understandable that the partial pressure can be any specific value of 70%, 71%, 72%, 73%, 74%, 75%, 76%, 77%, 78%, 79%, 80% or any value within the range of 70-80%.
[0050] According to another aspect of the present invention, there is also provided a use of the above-mentioned polyethylene resin for rotational molding or the polyethylene resin for rotational molding prepared according to the above-mentioned preparation method in a military packaging box.
[0051] The present invention will be described in detail by way of examples. It should be understood that the following examples are only used to further explain and illustrate the content of the present invention, and are not intended to limit the present invention. Among them, Example 1 of the present invention is the best embodiment.
[0052] The chemical additives used in the examples and comparative examples of the present invention are all commercially available, and their specific information is as follows:
[0053] Methylaluminoxane: purchased from Akzo Nobel; silica: purchased from Grace Davison; bis(1-butyl-3-methylcyclopentadienyl)zirconium dichloride, dimethylsilylbis(2-methyl-4-phenylindenyl)zirconium dichloride: purchased from Wuxi Yaodexin Chemical Products Co., Ltd.; butene, 1-hexene, octene, toluene, hexane: analytical grade, purchased from Aladdin Reagent Co., Ltd.
[0054] Example 1
[0055] The method for preparing a polyethylene resin for rotational molding described in this embodiment comprises the following steps:
[0056] (1) Methylaluminoxane and carrier silica are mixed in a mass ratio of 1:1, and a toluene solution of bis(1-butyl-3-methylcyclopentadienyl) zirconium dichloride and dimethylsilylbis(2-methyl-4-phenylindenyl) zirconium dichloride is added, stirred evenly, washed with hexane, filtered, and dried at 50° C. for 1 hour to obtain a metallocene catalyst; wherein the molar ratio of the bis(1-butyl-3-methylcyclopentadienyl) zirconium dichloride and the dimethylsilylbis(2-methyl-4-phenylindenyl) zirconium dichloride is 1:0.2, and the molar ratio of the methylaluminoxane to the sum of the bis(1-butyl-3-methylcyclopentadienyl) zirconium dichloride and the dimethylsilylbis(2-methyl-4-phenylindenyl) zirconium dichloride is 100:1;
[0057] (2) Add the metallocene catalyst to a Unipol gas phase polyethylene device, introduce 1-hexene and ethylene at a molar ratio of 0.01:1, and the molar concentration ratio of the metallocene catalyst to ethylene is 0.20, introduce hydrogen as a chain transfer agent, adjust the ethylene partial pressure in the polymerization reaction to 75%, and the hydrogen concentration to 600 ppm, and carry out gas phase polymerization at a polymerization temperature of 85° C. and a polymerization pressure of 2.0 MPa to obtain the polyethylene resin for rotational molding.
[0058] Example 2
[0059] The method for preparing a polyethylene resin for rotational molding described in this embodiment comprises the following steps:
[0060] (1) Methylaluminoxane and carrier silica are mixed in a mass ratio of 2:1, and a toluene solution of bis(1-butyl-3-methylcyclopentadienyl) zirconium dichloride and dimethylsilylbis(2-methyl-4-phenylindenyl) zirconium dichloride is added, stirred evenly, washed with hexane, filtered, and dried at 60° C. for 1 hour to obtain a metallocene catalyst; wherein the molar ratio of the bis(1-butyl-3-methylcyclopentadienyl) zirconium dichloride and the dimethylsilylbis(2-methyl-4-phenylindenyl) zirconium dichloride is 1:0.1, and the molar ratio of the methylaluminoxane to the sum of the bis(1-butyl-3-methylcyclopentadienyl) zirconium dichloride and the dimethylsilylbis(2-methyl-4-phenylindenyl) zirconium dichloride is 20:1;
[0061] (2) Add the metallocene catalyst to a Unipol gas phase polyethylene device, introduce butene and ethylene at a molar ratio of 0.05:1, and the molar concentration ratio of the metallocene catalyst to ethylene is 0.20, introduce hydrogen as a chain transfer agent, adjust the ethylene partial pressure in the polymerization reaction to 70%, and the hydrogen concentration to 500 ppm, and carry out gas phase polymerization at a polymerization temperature of 80° C. and a polymerization pressure of 2.5 MPa to obtain the polyethylene resin for rotational molding.
[0062] Example 3
[0063] The method for preparing a polyethylene resin for rotational molding described in this embodiment comprises the following steps:
[0064] (1) Methylaluminoxane and carrier silica are mixed at a mass ratio of 1.5:1, and a toluene solution of bis(1-butyl-3-methylcyclopentadienyl) zirconium dichloride and dimethylsilylbis(2-methyl-4-phenylindenyl) zirconium dichloride is added, stirred evenly, washed with hexane, filtered, and dried at 50° C. for 1 hour to obtain a metallocene catalyst; wherein the molar ratio of the bis(1-butyl-3-methylcyclopentadienyl) zirconium dichloride and the dimethylsilylbis(2-methyl-4-phenylindenyl) zirconium dichloride is 1:0.5, and the molar ratio of the methylaluminoxane to the sum of the bis(1-butyl-3-methylcyclopentadienyl) zirconium dichloride and the dimethylsilylbis(2-methyl-4-phenylindenyl) zirconium dichloride is 500:1;
[0065] (2) Add the metallocene catalyst to a Unipol gas phase polyethylene device, introduce octene and ethylene at a molar ratio of 0.03:1, and the molar concentration ratio of the metallocene catalyst to ethylene is 0.20, introduce hydrogen as a chain transfer agent, adjust the ethylene partial pressure in the polymerization reaction to 80%, and the hydrogen concentration to 1000 ppm, and carry out gas phase polymerization at a polymerization temperature of 90° C. and a polymerization pressure of 2.0 MPa to obtain the polyethylene resin for rotational molding.
[0066] Comparative Example 1
[0067] The preparation method of the polyethylene resin for rotational molding in this comparative example is exactly the same as that in Example 1, except that the molar ratio of bis(1-butyl-3-methylcyclopentadienyl)zirconium dichloride to dimethylsilylbis(2-methyl-4-phenylindenyl)zirconium dichloride in step (1) is 1:0.05; that is, the detailed steps of step (1) are: methylaluminoxane and carrier silica are mixed in a mass ratio of 1:1, bis(1-butyl-3-methylcyclopentadienyl)zirconium dichloride and dimethylsilylbis(2-methyl-4-phenylindenyl)zirconium dichloride are added, and the mixture is stirred for 2 hours. The invention discloses a method for preparing a metallocene catalyst comprising the steps of: preparing a toluene solution of bis(1-butyl-3-methylcyclopentadienyl) zirconium dichloride, stirring the solution evenly, washing the solution with hexane, filtering the solution, and drying the solution at 50°C for 1 hour to obtain a metallocene catalyst; wherein the molar ratio of the bis(1-butyl-3-methylcyclopentadienyl) zirconium dichloride to dimethylsilylbis(2-methyl-4-phenylindenyl) zirconium dichloride is 1:0.05, and the molar ratio of the methylaluminoxane to the sum of the bis(1-butyl-3-methylcyclopentadienyl) zirconium dichloride and dimethylsilylbis(2-methyl-4-phenylindenyl) zirconium dichloride is 100:1.
[0068] Comparative Example 2
[0069] The preparation method of the polyethylene resin for rotational molding in this comparative example is exactly the same as that in Example 1, except that the molar ratio of bis(1-butyl-3-methylcyclopentadienyl)zirconium dichloride to dimethylsilylbis(2-methyl-4-phenylindenyl)zirconium dichloride in step (1) is 0.2:1; that is, the detailed steps of step (1) are: methylaluminoxane and carrier silica are mixed in a mass ratio of 1:1, bis(1-butyl-3-methylcyclopentadienyl)zirconium dichloride and dimethylsilylbis(2-methyl-4-phenylindenyl)zirconium dichloride are added, and the mixture is stirred for 2 hours. The invention discloses a method for preparing a metallocene catalyst comprising the steps of: preparing a toluene solution of bis(1-butyl-3-methylcyclopentadienyl) zirconium dichloride, stirring the solution evenly, washing the solution with hexane, filtering the solution, and drying the solution at 50°C for 1 hour to obtain a metallocene catalyst; wherein the molar ratio of the bis(1-butyl-3-methylcyclopentadienyl) zirconium dichloride to dimethylsilylbis(2-methyl-4-phenylindenyl) zirconium dichloride is 0.2:1, and the molar ratio of the methylaluminoxane to the sum of the bis(1-butyl-3-methylcyclopentadienyl) zirconium dichloride and dimethylsilylbis(2-methyl-4-phenylindenyl) zirconium dichloride is 100:1.
[0070] Comparative Example 3
[0071] The preparation method of the polyethylene resin for rotational molding of this comparative example is exactly the same as that of Example 1, except that in step (2), the molar ratio of 1-hexene to ethylene is 0.005:1; that is, the detailed steps of step (1) are: adding the metallocene catalyst to the Unipol gas phase process polyethylene device, introducing 1-hexene and ethylene in a molar ratio of 0.005:1, the molar concentration ratio of the metallocene catalyst to ethylene is 0.20, introducing hydrogen as a chain transfer agent, adjusting the ethylene partial pressure in the polymerization reaction to 75%, the hydrogen concentration to 600 ppm, and carrying out gas phase polymerization at a polymerization temperature of 85°C and a polymerization pressure of 2.0 MPa to obtain the polyethylene resin for rotational molding.
[0072] Comparative Example 4
[0073] The preparation method of the polyethylene resin for rotational molding in this comparative example is exactly the same as that in Example 1, except that in step (2), the molar ratio of 1-hexene to ethylene is 0.1:1; that is, the detailed steps of step (1) are: adding the metallocene catalyst to the Unipol gas phase process polyethylene device, introducing 1-hexene and ethylene in a molar ratio of 0.1:1, the molar concentration ratio of the metallocene catalyst to ethylene is 0.20, hydrogen is introduced as a chain transfer agent, the ethylene partial pressure in the polymerization reaction is adjusted to 75%, the hydrogen concentration is 600 ppm, and a gas phase polymerization reaction is carried out at a polymerization temperature of 85°C and a polymerization pressure of 2.0 MPa to obtain the polyethylene resin for rotational molding.
[0074] Performance Testing
[0075] (I) Conventional performance test: The polyethylene resins for rotational molding obtained in Examples 1-3 and Comparative Examples 1-4 were subjected to conventional performance tests according to the following method. The specific results are shown in Table 1.
[0076] (1) Density: Tested in accordance with GB / T1033.2-2010;
[0077] (2) Melt mass flow rate MFR: The melt flow index MFR is measured according to GB / T3682.1-2018, at 190°C and a load of 2.16 kg;
[0078] (3) α-olefin content in polyethylene resin: calculated by nuclear magnetic resonance method;
[0079] (4) Tensile yield stress: tested according to GB / T1040.2-2022, type I spline, tensile speed 50 mm / min;
[0080] (5) Nominal strain at break: tested according to GB / T1040.2-2022, type I spline, tensile speed 50 mm / min;
[0081] (6) Flexural modulus: tested according to GB / T9341-2008;
[0082] (7) Room temperature simply supported beam notched impact strength: tested in accordance with GB / T1043.1-2008;
[0083] (8) Vicat softening temperature: tested according to GB / T1633-2008A120 method;
[0084] (9) Environmental stress cracking resistance time: tested according to GB / T1842-2008, using condition B;
[0085] Table 1 Conventional performance data of Examples 1-3 and Comparative Examples 1-4
[0086]
[0087]
[0088] As shown in Table 1, the nominal strain at break, the room temperature simply supported beam notched impact strength, and the environmental stress cracking resistance time of the polyethylene resin in Examples 1-3 of the present invention are all very excellent, indicating that they have excellent impact resistance, environmental stress cracking resistance, and slow crack growth resistance. Comparative Example 1 is compared with Example 1. It can be seen that the content of bis(1-butyl-3-methylcyclopentadienyl)zirconium dichloride is high during the preparation of the catalyst of Comparative Example 1, and the performance indicators of the polyethylene resin such as the nominal strain at break, the room temperature simply supported beam notched impact strength, and the environmental stress cracking resistance time are significantly deteriorated, indicating that its impact resistance, environmental stress cracking resistance, and slow crack growth resistance are deteriorated. Comparison between Example 2 and Example 1 shows that the content of dimethylsilylbis(2-methyl-4-phenylindenyl)zirconium dichloride is high when the catalyst of Comparative Example 2 is prepared, and the performance indicators such as nominal strain at break, simple beam notched impact strength at room temperature, and environmental stress cracking resistance time of the obtained polyethylene resin are significantly deteriorated, indicating that its impact resistance, environmental stress cracking resistance, and slow crack growth resistance are also deteriorated. Comparison between Example 3 and Example 1 shows that the amount of 1-hexene used in Comparative Example 3 is too small, and the nominal strain at break, simple beam notched impact strength at room temperature, and environmental stress cracking resistance time of the obtained polyethylene resin are significantly deteriorated. Comparison between Example 4 and Example 1 shows that the amount of 1-hexene used in Comparative Example 4 is too large, and the tensile yield stress and flexural modulus of the obtained polyethylene resin are significantly deteriorated.
[0089] (II) Continuous self-nucleation annealing heat graded SSA test: The polyethylene resins for rotational molding obtained in Examples 1-3 and Comparative Examples 1-4 were subjected to continuous self-nucleation annealing heat graded SSA test, and the specific steps are as follows:
[0090] Using a differential scanning calorimeter (TA Company, USA, model TAQ200), in a nitrogen atmosphere, the polyethylene sample was heated from room temperature to 160°C at 10°C / min, kept at this temperature for 3 min to eliminate the thermal history; cooled to 0°C at 10°C / min, kept at this temperature for 5 min; and heated to the nucleation temperature T at 10°C / min. S , stay for 5 minutes; cool down to 0℃ at 10℃ / min, stay for 5 minutes, and complete a self-nucleation process. Record the classification results of polyethylene self-nucleation annealing at 129℃, 125℃, 120℃, 114℃, 108℃, 103℃, 98℃, 94℃, and 89℃. After the classification, finally heat up to 160℃ at a rate of 10℃ / min, and record the final melting curve. The relative peak area is the mass fraction of the crystalline fraction. The specific results are shown in Table 2 and Figure 1-2 shown.
[0091] Table 2 SSA data of polyethylene resin in Examples 1-3 and Comparative Examples 1-4
[0092]
[0093]
[0094]
[0095] Figure 1 is the melting curve of the polyethylene resin after continuous self-nucleation annealing heat classification in Example 1, Figure 2 It is the melting curve of the polyethylene resin after continuous self-nucleation annealing and thermal classification in Comparative Example 1 of the present invention. Figure 1 and Figure 2 In the figure, the horizontal axis is temperature and the vertical axis is heat flow rate, which means the amount of heat that needs to be absorbed per second per gram of sample at a certain temperature when the temperature rises at a set rate. Figure 1 and Figure 2 The vertical coordinate value of the melting curve in is negative, indicating that the sample is absorbing heat at this time. Each peak represents a melting peak. The peak area represents the mass fraction of the crystalline fraction. The larger the peak area, the larger the mass fraction of the crystalline fraction in the corresponding temperature range. As the melting temperature decreases, the short chain content gradually increases, the lamellae are thinner, and the methylene sequence is shorter.
[0096] Through Table 2 and Figure 1-2By integrating the peak areas of the peaks in the above, it can be known that the content of the fractions above 120°C obtained by continuous self-nucleation annealing heat fractionation of the polyethylene resins in Examples 1-3 of the present invention is 45-55wt%, the content of the fractions above 116-120°C is 15-20wt%, the content of the fractions above 111-115°C is 10-15wt%, the content of the fractions above 100-110°C is 11-15wt%, and the content of the fractions below 98.5°C is 8-10wt%. It can be known from Example 1 and Comparative Examples 1 and 2 that the content of the fractions above 120°C of the polyethylene resin in Comparative Example 1 is less than 42wt%, and the content of the fractions above 120°C of the polyethylene resin in Comparative Example 2 is greater than 71wt%, indicating that the content of the fractions with less branches in the polyethylene resin is low or high; in addition, the fraction contents of the polyethylene resins at other temperatures in Comparative Examples 1 and 2 are also quite different from those in Example 1. It can be seen from Example 1 and Comparative Examples 3 and 4 that the content of the fraction of the polyethylene resin above 120°C in Comparative Example 3 is greater than 80wt%, and the content of the fraction of the polyethylene resin above 120°C in Comparative Example 4 is less than 45wt%, indicating that the content of the fraction with fewer branches in the polyethylene resin is too high or too low.
[0097] (III) Lamellar Thickness Distribution Index: The lamellar thickness distribution index of the polyethylene resin for rotational molding obtained in Examples 1-3 and Comparative Examples 1-4 is shown in Table 3. The lamellar thickness distribution index characterizes the uniformity of lamellar thickness distribution. The larger the index, the more uneven the comonomer distribution is and the worse the regularity of the material is.
[0098] Table 3 Lamellar Thickness Distribution Index of Polyethylene Resin in Examples 1-3 and Comparative Examples 1-4
[0099]
[0100] As shown in Table 3, the weight average sequence length distribution index of the polyethylene resin in Examples 1-3 of the present invention is between 1.15-1.18, and the Z average sequence length distribution index is between 1.25-1.28, indicating that the lamella thickness distribution of the polyethylene resin of the present invention is more uniform. As shown in Example 1 and Comparative Examples 1-4, the weight average sequence length distribution index and the Z average sequence length distribution index of the polyethylene resin in Comparative Examples 1-4 are higher than those in Example 1, indicating that the regularity of the polyethylene resin in Comparative Examples 1-4 is poor.
[0101] (IV) Full Notch Creep Tensile Test (FNCT): Full Notch Creep Tensile Test (FNCT) is an effective means to evaluate the slow crack growth resistance of materials. The samples of polyethylene resin for rotational molding in Examples 1-3 and Comparative Examples 1-4 were subjected to full notch creep tensile test (FNCT). The test was carried out in accordance with ISO16770:2004 (E). The specification of the sample strip was (90×6×6) mm. A circular incision was made on the square cross section of the sample strip. The four sides of the incision were on the same plane and the incision depth was 1 mm. The sample was placed in a 50°C, 2% TX-10 solution and a constant stress was applied. The failure time of the test strip under different stresses was tested. The specific results are shown in Table 4.
[0102] Table 4 FNCT results of polyethylene resin tableting samples in Examples 1-3 and Comparative Examples 1-4 (h)
[0103]
[0104]
[0105] As shown in Table 4, the polyethylene resins synthesized in Examples 1-3 of the present invention have longer failure times under different loads, indicating that the polyethylene resins of the present invention have excellent resistance to slow crack growth. As shown in Example 1 and Comparative Examples 1-4, the failure times of the polyethylene resins obtained in Comparative Examples 1-4 under different loads are significantly lower than that in Example 1, indicating that the polyethylene resins in Comparative Examples 1-4 have poor resistance to slow crack growth.
[0106] It can be seen that the present invention provides a special method for preparing polyethylene resin, especially designs a specific metallocene catalyst by regulating the molar ratio of bis(1-butyl-3-methylcyclopentadienyl)zirconium dichloride and dimethylsilylbis(2-methyl-4-phenylindenyl)zirconium dichloride, and then regulates the microstructure of the synthesized polyethylene resin, so that the fraction content in different temperature ranges obtained by the continuous self-nucleation annealing thermal grading test is regulated, so that the polyethylene resin has excellent impact resistance, environmental stress cracking resistance and slow crack growth resistance, and is suitable for military packaging boxes.
[0107] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not limitations on the implementation methods of the present invention. For ordinary technicians in the relevant field, other different forms of changes or modifications can be made on the basis of the above description. It is impossible to list all the implementation methods here. All obvious changes or modifications derived from the technical solution of the present invention are still within the protection scope of the present invention.
Claims
1. A polyethylene resin for rotational molding, characterized in that The polyethylene resin is a copolymer of ethylene and α-olefin; the polyethylene resin is subjected to a continuous self-nucleation annealing heat grading test, and the content of the fraction above 120°C is 45-55wt%, the content of the fraction between 116-120°C is 15-20wt%, the content of the fraction between 111-115°C is 10-15wt%, the content of the fraction between 100-110°C is 11-15wt%, and the content of the fraction below 98.5°C is 8-10wt%.
2. The polyethylene resin for rotational molding according to claim 1, characterized in that: The α-olefin is at least one selected from butene, hexene and octene.
3. The polyethylene resin for rotational molding according to claim 1, characterized in that: The content of α-olefin in the polyethylene resin is 1.18-1.92 mol%.
4. The polyethylene resin for rotational molding according to claim 1, characterized in that: The polyethylene resin has one or more of the following characteristics: The density of the polyethylene resin is 0.931-0.935 g / cm 3 ; The weight average sequence length distribution index of the polyethylene resin is 1.15-1.
18.
5. A method for preparing the polyethylene resin for rotational molding according to any one of claims 1 to 4, characterized in that: The steps include: (1) methylaluminoxane and carrier silica are mixed in a mass ratio of 1-2:1, a toluene solution of bis(1-butyl-3-methylcyclopentadienyl)zirconium dichloride and dimethylsilylbis(2-methyl-4-phenylindenyl)zirconium dichloride is added, the mixture is stirred evenly, washed, filtered, and dried to obtain a metallocene catalyst; (2) Adding the metallocene catalyst into a Unipol gas phase process polyethylene device, introducing α-olefin and ethylene in a molar ratio of 0.01-0.05:1, introducing hydrogen as a chain transfer agent, and performing a gas phase polymerization reaction at a polymerization temperature of 80-90° C. and a polymerization pressure of 2.0-2.5 MPa to obtain the polyethylene resin for rotational molding.
6. The method for preparing the polyethylene resin for rotational molding according to claim 5, characterized in that: In step (1), the molar ratio of bis(1-butyl-3-methylcyclopentadienyl)zirconium dichloride to dimethylsilylbis(2-methyl-4-phenylindenyl)zirconium dichloride is 1:0.1-0.
5.
7. The method for preparing the polyethylene resin for rotational molding according to claim 5, characterized in that: In step (1), the molar ratio of the methylaluminoxane to the sum of bis(1-butyl-3-methylcyclopentadienyl)zirconium dichloride and dimethylsilylbis(2-methyl-4-phenylindenyl)zirconium dichloride is 20-500:
1.
8. The method for preparing the polyethylene resin for rotational molding according to claim 5, characterized in that: In step (2), the concentration of hydrogen is 500-1000 ppm.
9. The method for preparing the polyethylene resin for rotational molding according to claim 5, characterized in that: In step (2), the partial pressure of ethylene in the gas phase polymerization reaction is 70-80%.
10. Use of the polyethylene resin for rotational molding according to any one of claims 1 to 4 or the polyethylene resin for rotational molding prepared according to the preparation method according to any one of claims 5 to 9 in military packaging boxes.
Citation Information
Patent Citations
Polymerization process of high-rigidity polyethylene rotational molding resin
CN106699943B
Rotomolded articles comprising metallocene-catalyzed polyethylene resin
CN107108993A
Method for rapidly detecting polyethylene tube special-purposed material grade
CN102954980A
Ethylene-butylene-octene terpolymer and preparation method and system thereof
CN115232239A
Polyethylene resin composition used for rotational moulding and rotational moulded product made with said composition
CN1281003A